Childhood, Youth Identity, and Violence in Formerly Displaced Communities in Uganda - Namuggala, Victoria Flavia (Critical Cultural Studies of Childhood, 2018)
This volume provides a critical assessment of the mainstream western childhood constructions and their impact to the developing world. Using African feminist and indigenous epistemological frameworks, the volume decolonizes the understanding of childhood, children, and youth. Specifically, the volume presents Global South contestations to mainstream western constructions by exploring alternative notions to standardized universal understanding of childhood. The author further deliberates childhood as a human right, exploring how armed violence hinders realization of such rights assessing humanitarian assistance during armed violence. Besides childhood, the volume explores the complex intersectional nature of youthhood and its cultural relevance to formerly displaced communities and how this manifests in access to and use of humanitarian assistance. .